Penatalaksanaan Keterlambatan Erupsi karena Impaksi Gigi 11 Secara Pembedahan dan Ortodontik (Laporan Kasus) - Arlette Suzy Puspa Pertiwi; Inne Suherna Sasmita; Jakobus Runkat (Faculty of Dentistry, Universitas Indonesia, 2015)
Delayed eruption is one of the the forms of dental eruption deviation characterized by delay of dental eruption. Delayed eruption can be caused by local factor such as impacted tooth. Treatment of the delayed eruption due to impacted tooth, which needs to be surgically exposed, bonded with a bracket and ligature or chain, and then orthodontically brought into the dental arch. We reported a case of a 12 years old girl who has non-erupted upper right permanent central incisor without the retention of upper right primary central incisor. Physical development was normal. 12,21,22, already erupted. Panoramic examination shows impacted 11 in the alveolar bone with the completion of apex formation. After the cephalometric and model analysis, we placed the fixed orthodontic appliances followed by surgical exposure to open the impacted area then place an orthodontic bracket with an attached chain to apply orthodontic forces on the tooth to aid in its movement into the line of occlusion.